(untitled) (Revista Apotheke, 2025)
This article analyzes the initial training of Visual Arts teachers based on the concept of profartistar, understood as a pedagogical-artistic action that transforms teaching into aesthetic expression. The study is grounded in A/R/Tography and the perspective of the classroom as a work of art, in dialogue with authors such as Mendes (2019), Rodeghiero (2019), and Freire (2006). Profartistar is presented as a practice that integrates art, life, and education through aesthetic experiments and experiences, capable of sensitizing developing bodies and enhancing more critical, reflective, and affective teaching-learning processes. The methodology adopted consisted of pedagogical proposals developed during a teaching internship in the Visual Arts undergraduate program at the Federal University of Pelotas. The activities involved the creation of collective mosaics in urban spaces and the use of logbooks, allowing students to record perceptions and emerging meanings of their practices. The analysis of the records revealed the relevance of aesthetic experiences for the construction of singular and collective meanings, awakening feelings, memories, and reflections on teaching, art, and life. The results indicate that profartistar fosters the sensitive development of future teachers, promoting an education that goes beyond the mere transmission of content, stimulating creativity, critical thinking, and the appreciation of experience as formative knowledge. It is concluded that this approach contributes to the development of educators capable of articulating art and life in their practices, empowering the classroom as a space for occurrence, transformation, and resistance in the face of contemporary challenges.